How public health teams navigate their different roles in alcohol premises licensing: ExILEnS multistakeholder interview findings - Rachel O'Donnell; Andrea Mohan; Richard Purves; Nason Maani; Matt Egan; Niamh Fitzgerald (NIHR Journals Library, 2022)
Background: In England and Scotland, local governments regulate the sale of alcohol by awarding licences to premises to permit the sale of alcohol for consumption on or off the premises, under certain conditions; without such a licence, alcohol cannot be legally sold. In recent years, many local public health teams have become proactive in engaging with alcohol licensing, encouraging licensing authorities to act in ways intended to improve population health. Objective: This research aimed to explore and understand the approaches and activities of public health stakeholders (i.e. NHS staff and other public health professionals) in seeking to influence local alcohol licensing policy and decisions, and the views of licensing stakeholders (i.e. licensing officers/managers, police staff with a licensing remit, elected members and licensing lawyers/clerks) on the acceptability and effectiveness of these approaches. Participants: Local public health teams in England and Scotland were directly informed about this multisite study. Scoping calls were conducted with interested teams to explore their level of activity in alcohol licensing from 2012 across several categories. Twenty local authority areas with public health teams active in licensing matters were recruited purposively in England (n = 14) and Scotland (n = 6) to vary by region and rurality. Fifty-three in-depth telephone interviews (28 with public health stakeholders and 25 with licensing stakeholders outside health, such as local authority licensing teams/lawyers or police) were conducted. Interview transcripts were analysed thematically in NVivo 12 (QSR International, Warrington, UK) using inductive and deductive approaches. Results: Public health stakeholders' approaches to engagement varied, falling into three main (and sometimes overlapping) types. (1) Many public health stakeholders in England and all public health stakeholders in Scotland took a 'challenging' approach to influencing licensing decisions and policies. Reducing health harms was felt to necessitate a focus on reducing availability and generating longer-term culture change, citing international evidence on the links between availability and alcohol-related harms. Some of these stakeholders viewed this as being a narrow, 'nanny state' approach, whereas others welcomed public health expertise and its evidence-based approach and input. (2) Some public health stakeholders favoured a more passive, 'supportive' approach, with some reporting that reducing availability was unachievable. They reported that, within the constraints of current licensing systems, alcohol availability may be contained (at least in theory) but cannot be reduced, because existing businesses cannot be closed on availability grounds. In this 'supportive' approach, public health stakeholders supplied licensing teams with data on request or waited for guidance from licensing teams on when and how to get involved. Therefore, public health action supported the licensing team in their aim of promoting 'safe' and 'responsible' retailing of alcohol and/or focused on short-term outcomes other than health, such as crime. (3) Some public health stakeholders favoured a 'collaborative' approach in which they worked in close partnership with licensing teams; this could include a focus on containing availability or responsible retail of alcohol, or both. Conclusions: In engaging with alcohol licensing, public health stakeholders adapted their approaches, sometimes resulting in a diminished focus on public health goals. Sampling did not include lower-activity areas, in which experiences might differ. The extent to which current licensing systems enable achievement of public health goals is questionable and the effectiveness of public health efforts merits quantitative evaluation. Study registration: The study is registered with the Research Registry as researchregistry6162. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme and will be published in Public Health Research. See the NIHR Journals Library website for further project information.